Helicopter vibration health monitoring systems featuring engine vibration monitoring - Bendisch, S.; Lamazere, F.; Camerini, V.; Naccarato, G.; Streiff, P. (My University, 2017)
Airbus Helicopter’s Health Monitoring System (HMS) offers a broad range of functions like rotor tuning, vibration health monitoring of the helicopter drive train and Engine Vibration Monitoring (EVM). For the latter, Airbus Helicopters cooperates with Safran Helicopter Engines concerning system design and performance for data collection, data processing and data transfer to assure the maximum of benefit for the customer. A clear objective is to provide HUM system compliant with regulations and guidelines from UK CAA, CAA Norway, industry associations like SAE and working groups like IHST. Classical vibration based health algorithms require information from analogic speed sensors for signal processing methods like order tracking, averaging and feature extraction. Airbus Helicopters proposes an approach without analogic speed interface, but extracting necessary information from the vibration with approximation given from digital speed signals. This technique makes use of the engine speeds which are collected by baseline helicopter systems and thus omitting any additional electrical interfaces of the HMS with the engine speed sensors. This paper presents the approach used by Airbus Helicopters in cooperation with Safran Helicopter Engines in the area of feature extraction and condition indicator computation using vibration signals and digital information from Engine Electronical Control Unit (EECU) through the helicopter avionic system HELIONIX®.